Dampak Ketergantungan Teknologi Terhadap Kualitas Pelayanan dan Ketahanan Operasional: Studi Kasus di Rumah Sakit Umum Daerah Kota Mataram - Mohammad Jihad Akbar (Jurnal Ragam Pengabdian, 2026)
Digital transformation in hospitals through SIMRS and Bridging System improves efficiency but creates operational vulnerabilities due to high technological dependence. System disruptions often hinder service flow and affect patient satisfaction. This study aims to analyse the impact of technological disruptions on service quality dimensions (SERVQUAL), identify the root causes of vulnerabilities, and formulate an operational resilience framework. This study uses a qualitative method with a case study approach at the Mataram City Hospital. Data were collected through in-depth interviews with five key informants (Head of Medical Records and admissions staff) and participatory observation. Data analysis used abductive thematic analysis techniques. Findings show that technological disruptions reduce the reliability and responsiveness dimensions. However, temporary manual procedures are able to maintain the assurance dimension. The strategies currently implemented are still single-loop learning (reactive), which creates double handling. A transition to double-loop learning is needed through the development of offline mode features and automatic synchronisation to transform the service recovery system into a more efficient one without burdening medical staff.